Malaysia kita : panduan dan rujukan untuk peperiksaan am kerajaan. (Kuala Lumpur International Law Book Services, 2000)
Public administration system in Malaysia.
Includes bibliographical references (p. 599).
Keywords: Malaysia -- Politics and government